Outcomes of Endovascular Aneurysm Repair using the Ovation Stent Graft System in Adverse Anatomy. (April 2018) - Greaves, Nicholas S.; Moore, Aiden; Seriki, Dare; Ghosh, Jonathan
Abstract : Objective: The aim was the evaluation of mid-term efficacy and safety outcome measures for the Ovation (Endologix, Santa Rosa, CA, USA) stent graft system in the management of infrarenal abdominal aortic aneurysms (iAAA) with adverse anatomy. Methods: A retrospective observational study of all patients undergoing elective iAAA repair was carried out from 2012 to 2017 using Ovation Prime or iX stent grafts with a minimum of 3 months follow-up at a single UK vascular centre. Post-operative surveillance involved computed tomography scans at 3 months and 1 year, with duplex ultrasound yearly thereafter. Outcome measures were established with retrospective analysis of pre- and post-operative imaging, and included peri-operative mortality, major adverse events, limb complications, aneurysm diameter change, and endoleak rates. All patients were within Ovation instructions for use (IFU), and assessment was made to determine whether aneurysms had anatomical features considered adverse for other commonly used stent graft platforms. Results: Ovation stent grafts were implanted in 52 patients (79% male, mean age 75.7 years) with a mean aneurysm diameter of 62.5 mm (range 55–107 mm). There was 100% technical deployment success. The 30 day mortality was 0% and there was no aneurysm related mortality during follow-up (median 24 months, range 3–48 months). There were no type I or III endoleaks, but 19% developed type II endoleaks with one patient requiring re-intervention. No iliac limb occlusions were identified but one case required relining for limb kinking. All 52 cases were within the IFU for Ovation but only 12% met the IFU criteria for the Cook and Medtronic devices. Conclusions: The mid-term experience with Ovation demonstrates safe, durable treatment of iAAAs, including those with unfavourable anatomy, frequently off IFU for other commonly used devices.